2009
DOI: 10.1111/j.1365-2265.2008.03376.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of iodine metabolism genes in human thyroid tissues: evidence for age and BRAFV600E mutation dependency

Abstract: The finding of higher PDS, TPO and TSH-R mRNA expression in paediatric vs. adult primary tumour tissues supports the hypothesis that this might contribute to the increased functional activity of metastases in the paediatric group. The finding that mRNA expression of the target genes in NTT was not age dependent does not provide an explanation for the higher susceptibility in the paediatric group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…CPTC tended to have more mutations than FVPTC. These results replicate the findings of smaller and comparable studies, although it is worth noting that the proportion of BRAF mutations detected in this study is on the higher end of the previous data [21][22][23][24][25]. In addition, our study used a strict clinical definition of FVPTC, including only FVPTC with classic features and eliminating the possibility of the "dilution effect" of benign mimics of FVPTC.…”
Section: Discussionsupporting
confidence: 91%
“…CPTC tended to have more mutations than FVPTC. These results replicate the findings of smaller and comparable studies, although it is worth noting that the proportion of BRAF mutations detected in this study is on the higher end of the previous data [21][22][23][24][25]. In addition, our study used a strict clinical definition of FVPTC, including only FVPTC with classic features and eliminating the possibility of the "dilution effect" of benign mimics of FVPTC.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, it has been suggested that the expression of NIS, as well as other proteins involved in iodine uptake and metabolism in pediatric patients, is higher than their expression in adults (Patel et al 2002, Faggiano et al 2004, Espadinha et al 2009). Nonetheless, in some series, there is a higher prevalence of extrathyroidal extension, regional lymph node involvement and distant metastases in younger children than in adolescents (Alessandri et al 2000, Jarzab et al 2005, Dinauer et al 2008, Lazar et al 2009, O'Gorman et al 2010, Rivkees et al 2011, Francis et al 2015.…”
Section: Other Fusions Transcriptsmentioning
confidence: 99%
“…Either younger children were commonly underrepresented and/or patients over the age of 18 years at diagnosis were also included into the pediatric group. Moreover, only two studies specifically addressed the expression of iodinemetabolizing genes in pediatric patients (Patel et al 2002, Espadinha et al 2009). The former study assessed the expression of NIS in the malignant tumor and compared to benign lesions as a substitute of normal thyroid.…”
Section: Other Fusions Transcriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. RET/PTC rearrangements predominantly occur in younger patients especially before the age of 20 while the BRAF mutation is almost exclusively detected in patients beyond the age of 20 years [4]. Patients with BRAF mutation are, therefore, at a greater risk to die of other causes in the follow-up.…”
Section: Discussionmentioning
confidence: 98%